Archetypal Nonviolence - Cunningham, Renee Moreau, author.
1 online resource
Keywords: Rene Moreau Cunningham's unique study utilizes the psychology of C. G. Jung and the spiritual teachings of Mahatma Gandhi and Martin Luther King, Jr. to explore how nonviolence works psychologically as a form of spiritual warfare, confronting and transmuting aggression. Archetypal Nonviolence uses King's iconic march from Selma to Montgomery, a demonstration which helped introduce America to nonviolent philosophy on a mass scale, as a metaphor for psychological and spiritual activism on an individual and collective level. Cunningham's work explores the core wound of racism in America on both a collective and a personal level, investigating how we hide from our own potential for evil and how the divide within ourselves can be bridged. The book demonstrates that the alchemical transmutation of aggression through a nonviolent ethos, as shown in the Selma marches, is important to understand as a beginning to something greater within the paradox of human violence and its bedfellow, nonviolence. Archetypal Nonviolence explores how we can truly transform hatred by understanding how it operates within. It will be of great interest to Jungian analysts and analytical psychologists in practice and in training, and to academics and students of Jungian and post-Jungian studies, American history, race and racism, and nonviolent movements.